Beyond Clinical Efficacy: A Literature Review on the Safety Challenges of Isotretinoin Therapy - Patrzykąt, Klaudia Martyna; Puchalski, Konrad; Liszka, Paweł; Perediatkiewicz, Jakub; Zasiadła, Marta; Olejnik-Chlewicka, Klaudia; Urbański, Wojciech; Łuczak, Paweł Mateusz; Brodowski, Jakub; Ogórek, Agata (Quality in Sport, 2026)
Background. Acne vulgaris is a chronic inflammatory skin condition that often leads to scarring and psychological distress. Oral isotretinoin is the most effective systemic medication for severe or treatment-resistant acne, but concerns about its adverse effects remain. Aim. This review summarizes the current state of knowledge on isotretinoin in acne therapy, highlighting safety issues and implications for everyday clinical practice. Material and methods. A narrative literature review was conducted using PubMed/MEDLINE for articles published between January 2016 and November 2025. Human studies and reviews on systemic isotretinoin for acne vulgaris treatment, along with selected articles providing relevant epidemiological and clinical context for acne, were included if they reported efficacy, remission, adverse effects, impact on tissue regeneration, or monitoring recommendations. Randomized trials, observational studies, systematic reviews, meta-analyses, and high-quality narrative reviews were eligible for inclusion. Non-acne indications, animal-only studies, and non-peer-reviewed publications were excluded. Results. Isotretinoin addresses all major pathogenic mechanisms of acne, leading to high clearance and long-term remissions. Mucocutaneous dryness is the most common adverse effect, but it is manageable with proper skincare. Laboratory abnormalities involve mild, reversible dyslipidemia and liver enzyme elevations. The most dangerous side effect is teratogenicity, which requires strict pregnancy-prevention programs. Studies have not confirmed an increased incidence of depression or inflammatory bowel disease; however, clinical monitoring remains essential. Musculoskeletal and ophthalmologic adverse effects are generally mild and dose-dependent. Conclusions. Structured risk management, regular clinical and laboratory checks, along with the lowest possible dose, enable safe and effective acne control through individualized isotretinoin treatment.